(untitled) (Research, Society and Development, 2021)
Psychological disorders suffered by sexually abused children, but specifically Post Traumatic Stress Disorder-PTSD. The research aims to analyze Post Traumatic Stress Disorder suffered by Sexually Abused Children. This research will have a qualitative approach of bibliographic character, having as research instrument textbooks on the subject, electronic portals of scientific journals between 2008 and 2021. In this step, 6 articles, 15 works published in journals and 3 books were used. Psychological care offers resources for understanding the disease process and coping strategies. In this case, psychological care after suffering sexual abuse is of paramount importance, so that the subject can expose what he is feeling and the professional can seek techniques to recover the that was taken from him. There is little information about therapeutic methods, as well as the absence of validated and effective psychological instruments for the clinical assessment of children and adolescents. It was observed that post-traumatic stress disorder is the most common in children victims of sexual abuse and that the Cognitive-Behavioral Theory is the model to be developed and applied to them.